Empire of pain : the secret history of the Sackler dynasty - Keefe, Patrick Radden, 1976- (Anchor Books, 2022)
"The Sackler name has adorned the walls of many storied institutions -- Harvard, the Metropolitan Museum of Art, Oxford, the Louvre. They are one of the richest families in the world, known for their lavish donations to the arts and the sciences. The source of the family fortune was vague, however, until it emerged that the Sacklers were responsible for making and marketing a blockbuster painkiller, OxyContin, that was the catalyst for the opioid crisis. 'Empire of Pain' is the saga of three generations of a single family and the mark they would leave on the world, a tale that moves from the bustling streets of early twentieth-century Brooklyn to the seaside palaces of Greenwich, Connecticut, and Cap d'Antibes to the corridors of power in Washington, D.C. The history of the Sackler dynasty is rife with drama--baroque personal lives; bitter disputes; fistfights in boardrooms; glittering art collections; Machiavellian courtroom maneuvers; and the calculated use of money to burnish reputations and crush dissent. 'Empire of Pain' is a masterpiece of narrative reporting--a grand, devastating portrait of the excesses of America's second Gilded Age, a study of impunity among the super elite, and an investigation of the naked greed and indifference to human suffering that built one of the world's great fortunes." --back cover